Implementation of Multifactor Authentication Using Optimistic Fair Exchange - M, Satheesh; M, Deepika (Journal of Ubiquitous Computing and Communication Technologies, 2020)
In this work, two participants fairly send or receive things through the aid of intermediate who is only engaged if required. An up-to-date accepted necessity is with the aim of involving third party in the trade should be transparent, to save from privacy and evade terrible publicity. Together, a dishonest intermediate will negotiate the fairness of the trade and so the intermediate should be liable in case of any behavioural changes. Optimistic fair exchange (OFE) is one of the classical protocols to assure fairness of indulgence for a party. This exchange can be done by means of an arbitrator. The most important aspect of OFE is to describe security models so as to capture real-time attacks and design schemes secure in practical models. Signaller is confirmed with the data to send the correct person to address that to make sure it is. Since then the SMS has gone through to achieve that can hold the path to the right to see which if any is the fact that to ensure there is. After the signature is created by creating it to be able to well take care of it and then to the right of the person to pay off that is sure to make it. In this project, to avoid the third party attack (hacking) and unauthorized person access the particular important data. The data should be transmitted in sender to receiver that receiver only have a correct data without any data losses, protect a data security in cyber-attacks. A signature may be digitally and OFE design for the exchanged item have trade-off between transparency and accountability.
Keywords: OFE; Network; Signaller; Message; Add signaller; View signaller; Add arbitrator; View arbitrator; Get trajectory; Find Sybil attack; Signal verification; Triple DES algorithm; Public key; Private Key; Cipher text; Plain text